Key Stakeholders of General Inclusive Education in Western Countries and Uzbekistan - Jalgasova , Korkem Allamurat qizi (The Lingua Spectrum, 2026)
This article presents a comparative analysis of the key stakeholders in general inclusive education within Western countries and Uzbekistan. Based on the theoretical foundations of comparative pedagogy, the study examines the roles, statuses, and interaction mechanisms of the child, parents, teachers, state bodies, and civil society. The analysis reveals that Western models are characterized by a horizontal, partnership-based structure where stakeholders operate with a high degree of autonomy and the child is recognized as a socially active subject. In contrast, the Uzbek model is undergoing a gradual institutionalization, initially shaped by a centralized, state-regulated vertical system. While normative frameworks are in place, the transition to a systemic, multidisciplinary, and collaborative model remains a crucial challenge. The article concludes that the effectiveness of inclusive education is not solely dependent on the presence of distinct actors but on the establishment of stable, systemic, and coordinated relationships based on mutual trust, shared responsibility, and joint decision-making.